2014
DOI: 10.1371/journal.pone.0093338
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Transcriptional Profiling of Skin and Dorsal Root Ganglia after Ultraviolet-B-Induced Inflammation

Abstract: Ultraviolet-B (UVB)-induced inflammation produces a dose-dependent mechanical and thermal hyperalgesia in both humans and rats, most likely via inflammatory mediators acting at the site of injury. Previous work has shown that the gene expression of cytokines and chemokines is positively correlated between species and that these factors can contribute to UVB-induced pain. In order to investigate other potential pain mediators in this model we used RNA-seq to perform genome-wide transcriptional profiling in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 62 publications
7
52
0
Order By: Relevance
“…Another study examined molecular changes after UVB irradiation at the transcriptional level using RNA sequencing. By comparing skin samples of patients and rodents exposed to UVB, the authors presented a remarkable level of similarity across the different species, identifying changes on over 800 common genes . Most of the changes in expression were found in the skin, as previously reported .…”
Section: Changes In Mrna Transcription and Protein Levels After Uvb Bsupporting
confidence: 57%
See 1 more Smart Citation
“…Another study examined molecular changes after UVB irradiation at the transcriptional level using RNA sequencing. By comparing skin samples of patients and rodents exposed to UVB, the authors presented a remarkable level of similarity across the different species, identifying changes on over 800 common genes . Most of the changes in expression were found in the skin, as previously reported .…”
Section: Changes In Mrna Transcription and Protein Levels After Uvb Bsupporting
confidence: 57%
“…Most of the changes in expression were found in the skin, as previously reported . Unsurprisingly, many of the genes upregulated were related to inflammation . The group also looked at molecular changes at the DRGs and identified 39 genes differentially regulated .…”
Section: Changes In Mrna Transcription and Protein Levels After Uvb Bsupporting
confidence: 55%
“…Although some studies have demonstrated that UV irradiation induces distinct chemokines, such as CCL3, CCL20, CXCL1, CXCL2, CXCL3 and CXCL5 in human skin, these studies did not examine the expression or function of chemokines in isolated human SC fat tissues. CXCL5 is a proinflammatory chemokine that is linked to adipose tissue inflammation and insulin resistance, which antagonizes insulin signalling via the JAK‐STAT pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has suggested that chromatin plays a major role in the UV-induced cellular response including regulation of gene expression changes (Andrade-Lima et al, 2015;Dawes et al, 2014;Dinant et al, 2013;Duan and Smerdon, 2014;Hassan et al, 2014;Izhar et al, 2015;Li et al, 2014;Sesto et al, 2002;Zhang et al, 2014). However, a detailed genomewide analysis to investigate the relationship of chromatin and gene expression changes was still missing.…”
Section: Discussionmentioning
confidence: 99%
“…Consequences of DNA lesions, either as a result of UV irradiation or other genotoxic agents, to cell physiology are widely governed by changes in gene expression regulated on various levels (AndradeLima et al, 2015;Bowden et al, 2015;Dawes et al, 2014;Sesto et al, 2002). UVB has been shown to inhibit initiation of transcription by impeding the binding of RNA polymerase II to the promoters of many transcribed genes (Gyenis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%